Assessment of the high risk and unmet need in patients with CAD and type 2 diabetes (ATHENA): US healthcare resource utilization, cost and burden of illness in the Diabetes Collaborative Registry. Issue 3 (7th May 2020) - Wittbrodt, Eric; Bhalla, Narinder; Andersson Sundell, Karolina; Gao, Qi; Dong, Liyan; Cavender, Matthew A.; Hunt, Phillip; Wong, Nathan D.; Mellström, Carl
Abstract: Background: THEMIS (NCT01991795) showed that in patients with type 2 diabetes (T2D) and stable coronary artery disease (CAD) but with no prior myocardial infarction (MI) or stroke, ticagrelor plus acetylsalicylic acid (ASA) decreased the incidence of ischaemic cardiovascular events compared with placebo plus ASA. To complement these findings, we assessed disease burden and healthcare resource utilization (HRU) in US patients with CAD and T2D, but without a prior MI or stroke. Methods: This observational study used 2013‐2014 data from the Diabetes Collaborative Registry linked to Medicare administrative claims. Two cohorts of patients with T2D were studied: patients at high cardiovascular risk (THEMIS‐like cohort; N = 56 040) and patients at high cardiovascular risk or taking P2Y12 inhibitors (CAD‐T2D cohort; N = 69 790). Outcomes included the composite of all‐cause death, MI and stroke; the individual events from the composite endpoint; HRU; and costs. Results: Median age was 73.0 years, and median follow‐up was 1.3 years in both cohorts. Event rates of the composite outcome were 16.34 (95% confidence interval: 16.31‐16.37) and 17.64 (17.61‐17.67) per 100 person‐years for the THEMIS‐like and CAD‐T2D cohorts, respectively. The incidence rate of bleeding events was 0.13 events per 100 person‐years in both cohorts. Healthcare costs per patient‐year were USD 8741 and USD 9150 in the THEMIS‐like and CAD‐T2D cohorts, respectively. Conclusions: Patients in the THEMIS‐like cohort and the broader CAD‐T2D population had similarly substantial cardiovascular event rates and healthcare costs, indicating that patients with CAD and T2D similar to the THEMIS population are at an increased cardiovascular risk. Abstract : Disease burden and healthcare resource utilization (HRU) were assessed in patients with coronary artery disease (CAD) and type 2 diabetes (T2D) from a US‐based diabetes registry. Patients similar to those enrolled in THEMIS have substantial cardiovascular event rates and healthcare costs, but low bleeding risk. Findings were similar in a broader CAD‐T2D population, indicating that the THEMIS population reflects high‐risk patients with CAD and T2D in clinical practice.